Peran Lembaga Sertifikasi Halal Dalam Memastikan Kepercayaan Konsumen: Studi Multi-Situs Di Indonesia - Nur Janah, Nadhivah; Nurul Hikmah; Imron Mustofa (Qawanin: Jurnal of Economic Syaria Law, 2025)
Halal certification bodies play a crucial role in building consumer confidence in halal products in Indonesia. This study, conducted in several locations, examined the views of Muslim consumers, producers, and certification bodies, particularly the Indonesian Ulema Council (MUI) and the Halal Product Guarantee Agency (BPJPH) in three different cities: Jakarta, Surabaya, and Makassar. Data collection was conducted through in-depth interviews, group discussions, and observations. The findings show that the reputation of the institution, clarity regarding halal standards, and transparency in certification information play an important role in strengthening consumer confidence. The various views of consumers in each city are influenced by the socio-cultural context and varying access to information. This research provides a meaningful contribution to the development of halal certification agency policies and practices, with the aim of improving certification effectiveness and supporting the sustainable growth of the national halal industry. Lembaga yang memberikan sertifikasi halal memiliki peran krusial dalam membangun kepercayaan konsumen terhadap produk halal di tanah air. Penelitian yang dilakukan di beberapa lokasi ini menyelidiki pandangan konsumen Muslim, produsen, serta lembaga sertifikasi, terutama Majelis Ulama Indonesia (MUI) dan Badan Penyelenggara Jaminan Produk Halal (BPJPH) di tiga kota yang berbeda: Jakarta, Surabaya, dan Makassar. Pengumpulan data dilakukan melalui wawancara mendalam, diskusi kelompok, dan observasi. Temuan penelitian menunjukkan bahwa reputasi lembaga, kejelasan mengenai standar halal, dan transparansi dalam informasi sertifikasi mempunyai peranan penting dalam memperkuat kepercayaan konsumen. Berbagai pandangan konsumen di setiap kota dipengaruhi oleh konteks sosial budaya serta akses informasi yang bervariasi. Penelitian ini memberikan sumbangsih yang berarti bagi pengembangan kebijakan dan praktik lembaga sertifikasi halal, dengan tujuan untuk meningkatkan efektivitas sertifikasi dan mendukung pertumbuhan industri halal nasional secara berkelanjutan.